STUDI TENTANG RESPON MASYARAKAT MISKIN TERHADAP PROGRAM JAMINAN KESEHATAN MASYARAKAT ( JAMKESMAS ) DIKELURAHAN SAIL KECAMATAN TENAYAN RAYA PEKANBARU - Tobing, Farida Naima; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The study on "Studies of the poor response to the health insurance program(Assurance ) in the Village District of Tenayan Raya Pekanbaru Sail". This studydescribes the characteristics of the intended recipient of a health card, health cardpublic response to the reception, and the expectations of society with a healthprogram. The response is the acceptance or rejection of the public with an innovationin the form of a government health card program. This y will look at the peopleusing the health card to get treatment or not use it for treatment. This study is locatedin the Village District of Sail Tenayan Kingdom and get as many as 12 subjects.Mechanical withdrawal of subjects in this study is the snowball method is to get thesubject to get a key informant who knows the community and further health cardrecipients get a health card recipient of the poor and the poor who do not receive ahealth card which is then interviewed by investigators. Analysis of the data in thisstudy conducted with qualitative methods which are then presented descriptively andsystematically. Based on the analysis of the data, the conclusion of the characteristicsof the beneficiaries of a health card that can be seen by observing the relative povertyhousing conditions, education level, income, number of family members. If thecharacteristics meet the poor people are entitled to a health card. The response of agiven society is receiving assistance programs and others do not receive. As for theexpectations of the poor is that the aid program can continue to run a health card andhealth card can be used for both medical treatment at health centers and hospitals thathave been previously set by the government. society also expects that the standard ofcare in hospitals further enhanced and standard services equated with public service.Keywords : Card JAMKESMAS , the Poor , Response.